Seeing the Wood for the Trees: Enhancing Metadata Subject Elements with Weights - Zhang, Hong; Smith, Linda C.; Twidale, Michael; Gao, Fang Huang (Information technology and libraries, 2011)
Subject indexing has been conducted in a dichotomous way in terms of what the information object is primarily about/of or not, corresponding to the presence or absence of a particular subject term, respectively. With more subject terms brought into information systems via social tagging, manual cataloging, or automated indexing, many more partially relevant results can be retrieved. Using examples from digital image collections and online library catalog systems, we explore the problem and advocate for adding a weighting mechanism to subject indexing and tagging to make web search and navigation more effective and efficient. We argue that the weighting of subject terms is more important than ever in today’s world of growing collections, more federated searching, and expansion of social tagging. Such a weighting mechanism needs to be considered and applied not only by indexers, catalogers, and taggers, but also needs to be incorporated into system functionality and metadata schemas.